O APPLICATION UNICASH - POINTS TRANSFER : POINTS TRANSFER (CIPEEX, 2022)
THE PRESENT WORK IS ONE OF THE RESULTS OF THE UNICASH MOBILE APPLICATION DEVELOPMENT. THE APPLICATION AIMS TO EARN REWARDS FOR TASKS AND MODULES COMPLETED IN THE VIRTUAL LEARNING ENVIRONMENT. THE SOFTWARE ENGINEERING COURSE OFFERED BY UNIVERSIDADE EVANGÉLICA DE GOIS, PROPOSED, THROUGH THE INTEGRATIVE DISCIPLINE PROGRAMMING FOR MOBILE DEVICES, A STUDY ON THE CONSTRUCTION OF A MOBILE APPLICATION, NAMED "UNICA$SH", WHOSE MAIN OBJECTIVE IS TO STIMULATE STUDENTS REGARDING THEIR ACADEMIC TASKS, SUCH AS THE DELIVERY OF WORK AND ACTIVITIES IN THE VIRTUAL LEARNING ENVIRONMENT, THE APPLICATION WILL REWARD THE STUDENT WHO FULFILLS THEIR DUTIES THROUGH POINTS THAT CAN BE USED TO OBTAIN DISCOUNTS ON PRODUCTS OR SERVICES FROM SOME COMMERCIAL POINTS WITHIN THE UNIVERSITY. AMONG THE MOST DIVERSE FEATURES OF UNICA$H, ONE OF THEM IS THE SO-CALLED €ŒPOINTS TRANSFER€ WHICH, AS THE NAME ITSELF SAYS, WOULD BE A WAY FOR THE STUDENT TO BE ABLE TO SEND HIS CONQUERED POINTS TO ANOTHER PERSON, SIMILAR TO PIX, THE NEW SYSTEM OF BRAZILIAN PAYMENTS LAUNCHED BY BACEN IN OCTOBER 2020.&NBSP;